Pendampingan Usaha Budidaya Bebek Berbasis Tiga Pilar Peternakan di Kecamatan Cileungsi - Wicaksana, Indrajit; Budiningsih, Susilowati; Primadhita, Yuridistya (Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
This business assistance is part of productive community service which aims to provide entrepreneurial knowledge in the field of animal husbandry using the three pillars. Partner, namely the Cuan Barokah duck farming business located in Cileungsi District, Bogor. Partner is provided with socialization and business assistance so it can conduct business analysis and find solutions to create increased business. In the aspect of feeding, partner is equipped with knowledge so the feeding process is more efficient. In the managing aspect, partner is provided with easy financial recording training and better sanitary system. In the breeding aspect, partner is trained so it can carry out nurseries independently. The existence of this training is expected to help create an increase in sustainable business capacity on Cuan Barokah  duck farming in Cileungsi District, Bogor Regency